Pemanfaatan Aplikasi Quizizz untuk Pembuatan Kuis bagi Guru PAUD Al-Ikhlas Salman Salamanmloyo Semarang - Budi Hartono; Veronica Lusiana; Sri Eniyati (Fakultas Teknologi Informasi dan Industri Unisbank, 2022)
In this new normal period, the Al-Ikhlas Salman Early Childhood Education Institution (PAUD) in Salamanmloyo, Semarang City, is again carrying out face-to-face or offline teaching and learning activities at schools. The community service team of the Faculty of Information Technology and Industry, Stikubank University Semarang, assisted in making interactive quizzes that were interesting and easy to understand by PAUD teachers. The process of making quizzes using the Quizizz application. Through this learning media application, it is hoped that students will more easily understand the learning material. Quiz materials include the introduction of colors, animals, numbers, basic shapes, as well as instructions for maintaining health. At the beginning of the teaching and learning process in this new normal, it is necessary to be refreshed on the right instructions to maintain health, so that teachers, students, parents, the surrounding community can carry out activities properly, comfortably, and stay alert. The preparation of learning materials is discussed with the teacher so that when it is taught it can be well received by students.